DAYA TARIK WISATA PADA DESTINASI WISATA KAWASAN KONSERVASI PENYU KOTA PARIAMAN SUMATERA BARAT - Nabila, Dewi Ayu; Yusrizal, Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Pariaman City is one of the regions in West Sumatra with a rapidly growing tourism sector. Its natural and cultural wealth has driven the transformation of Pariaman into a more developed tourist destination, particularly through marine and educational attractions such as the Sea Turtle Sanctuary. This study aims to identify the tourism appeal of the Turtle Conservation Area in Pariaman City. The research uses a qualitative method with a descriptive approach, involving observation, interviews, and documentation. The data analysis techniques include data collection, reduction, presentation, and drawing conclusions. The results show that: (1) the conservation area is unique due to its turtle ecosystem, clean beaches, clear sea, fresh air, and mangrove forests with distinctive roots that serve as educational objects; (2) the diversity of turtle species is an attraction, consisting of green turtles, hawksbill turtles, and olive ridley turtles; (3) hatchling release and mangrove planting activities provide educational and participatory experiences for tourists, especially students; (4) the Turtle Monument serves as a photo spot and symbolizes the conservation spirit within the area. Keywords: Attraction, Tourist Destination, Turtle Conservation Area